2018
DOI: 10.2176/nmc.oa.2017-0203
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy in Anterior Circulation Occlusion Could Be More Effective than Medical Management Even in Low DWI-ASPECTS Patients

Abstract: The purpose of this study was to investigate whether patients with low preoperative Diffusion-weighted Imaging Alberta Stroke Program Early Computed Tomography Score (DWI-ASPECTS) could benefit from mechanical thrombectomy for acute anterior circulation occlusion. This was a retrospective, non-blinded, cohort study. From September 2012 to August 2016, 83 consecutive patients of acute anterior circulation occlusion were treated with thrombectomy using second-generation devices or medical management. The DWI-ASP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 48 publications
(53 reference statements)
1
22
0
Order By: Relevance
“…Overall, 1194 patients (cases) underwent MT (stent retriever, aspiration-first thrombectomy or combined techniques), whereas 184 patients (controls) were treated with medical therapy (IVT for eligible patients or conservative management). Five studies16–20 compared outcomes between the MT group and the medical treatment group whereas 12 studies21–32 reported series of patients with low ASPECTS exclusively treated with MT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 1194 patients (cases) underwent MT (stent retriever, aspiration-first thrombectomy or combined techniques), whereas 184 patients (controls) were treated with medical therapy (IVT for eligible patients or conservative management). Five studies16–20 compared outcomes between the MT group and the medical treatment group whereas 12 studies21–32 reported series of patients with low ASPECTS exclusively treated with MT.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were retrospective series17–19 23 25 27–30 and eight studies had a prospective design 16 20–22 24 26 31 32. Two included series were prospective randomized trials 16 20.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings unanimously suggest that this subgroup of patients may have benefit comparable to those with higher ASPECTS. Ohta et al 18 demonstrated that this benefit is even more apparent when these low ASPECTS patients undergoing EVT are compared to a group who receive medical therapy alone. The strongest evidence comes from a subgroup analysis of a randomized controlled trial (THRACE) that showed a favorable trend (36% vs 26%) toward good (0-2) 90-day mRS in patients who undergo EVT and intravenous thrombolysis compared to those receiving intravenous thrombolysis only for patients with ASPECTS of 0-4.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have recently reported that the prognosis of mechanical thrombectomy is superior to that of medical treatment alone in patients with a low DWI-pc-ASPECTS score in the anterior circulation. [16][17][18] However, the characteristics and prognosis of acute BAO in patients with DWI-pc-ASPECTS of less than 6 have not been studied. Thus, we aimed to investigate the clinical characteristics and predictive prognostic factors for better clinical outcomes in acute BAO patients with DWI-pc-ASPECTS of less than 6 who underwent ERT.…”
Section: Introductionmentioning
confidence: 99%